Pengaruh Stress pada Ibu Hamil - Vivit selfiana; Nur Ulfadamayanti S; St.Maani St.Maani; Nuraini Nuraini; Sri Nurul fadillah (Journal on Education, 2023)
The purpose of this research is to determine the effect of stress on the mother pregnant. This study uses a qualitative descriptive method. Stress is a person's reaction both physically and emotionally (mentally/psychologically) if any changes in the environment that require a person to adapt. Stress is a natural and important part of life, but when it is heavy and for a long time can be detrimental to health. In pregnant women, serious and long-lasting stress can affectimmune system that protects the body from infection. When system compromised immune system, the risk of uterine infection and childbirth premature could be bigger. Based on the research conducted there is an effect of stress at the time pregnancy which causes many negative impacts on health. Based on observations, we know that due to the large number of cases of pregnant women having a miscarriage or premature birth and other problems mostly caused by stressful conditions. So that's what we should be learn to understand how to deal with stress, especially at times pregnant.